Comunity academic Project: way of action, participation and reflection to dialogue in the community (Praxis Educativa, 2020)
This paper emerges from a wider research project which seeks to unveil a core problem that underlies community academic projects developed in the municipalized university villages of the Sucre Mission. A pedagogical scenario emerges full of instructional practices being, leaving aside the nature of the project to be assumed from a critical and reflective vision. The findings were analyzed with different theories. Data collection techniques such as in-depth interview and testimony analysis were used. The results show that in the practices of the projects, permanent processes of community dialogue are not developed along with each of its participants, which becomes later obstacles to construct critical and reflective thinking.
Keywords: community academic project; action; reflection; participation; critical pedagogy